"You'd have to be blind not to see it..." Hertiage Chapel Chapel Service, February 9, 2009, Dr. Dan Mortensen - Valley Forge Christian College; Dan Mortensen; Valley Forge Christian College (Phoenixville, PA : Valley Forge Christian College, 2009)
Dr. Dan Mortensen plays the character of Meyer Berger, newspaper reporter for the New York TImes. He reads Berger's article, "The Stirring Story of an American Town, " which was published in the New York Times on May 19, 1943. The story tells the tale of the beginning of the Valley Forge General Hospital, its patients, and their affect and effect on the town and townspeople of Phoenixville, Pennsylvania.
Host: Dr. Dan Mortensen.